THE INTEGRATION OF CHARACTER EDUCATION IN ARTS AND CULTURE SUBJECT IN JUNIOR HIGH SCHOOL - Maras Fitriana; Alek Andika (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
The integration of character education in Arts and Culture subjects in junior high school combines the teaching of art skills with the cultivation of moral values such as discipline, responsibility, and empathy, forming intellectually and emotionally qualified students who are talented and virtuous. The research aims to analyze the effectiveness of the approach to integrating moral values through cultural arts, general curriculum, literature and religion in fostering students' responsibility, creativity, and social skills, as well as examining the role of teachers and stakeholder collaboration in the formation of holistic character. The research uses the Systematic Literature Review to identify, evaluate, and synthesize scientific evidence from relevant literature in a systematic and structured manner, starting with the formulation of research questions to comprehensive literature search strategies for an in-depth understanding of research phenomena. The integration of direct cultural arts such as dance and drawing fosters responsibility and unity despite resource constraints; a general curriculum approach to improving student morale through stakeholder collaboration; integration through literature and religion forms an identity with fun learning; Common implementation in schools creates a learning environment that supports moral values with teachers as a character-building model. This study concludes that the integration of cultural arts is directly effective in fostering moral values with the role of the central teacher; a general curriculum approach to improving morale through collaboration; the integration of literature-religion enriches a holistic character; General implementation optimizes student character development through stakeholder collaboration.